Powertrain configuration design for two mode power split hybrid electric vehicle - Tao Ke; Liangyi Nie; Andrés Kecskeméthy (Scientific Reports)
Abstract Hybrid transmissions have attracted great attention in the automotive industry due to their energy-saving, low-emission properties, and have become a focus of research and development. This paper presents a new method to design the configuration of two mode power split hybrid transmission using the combination of the simple planetary gear trains (PGT). For this purpose, the hybrid transmission structure is divided into two substructures, which achieve different operation modes respectively. Then the output of one substructure is reconnected with the components of another substructure to obtain the complete hybrid transmission configuration. In addition, by adding additional shifting elements, the hybrid configurations can also realize the fixed gear mode as a traditional automatic transmission. As a result, 38 hybrid transmissions are obtained, and the kinematic analysis of a new configuration is performed for the subsequent optimization. Furthermore, using this decomposition and recombination method, the hybrid transmissions with multiple PGTs and different operation modes can be synthesized by changing the predefined modes.